EFFECTS OF DIURETIC HORMONE 31, DROSOKININ, AND ALLATOSTATIN A ON TRANSEPITHELIAL K(+) TRANSPORT AND CONTRACTION FREQUENCY IN THE MIDGUT AND HINDGUT OF LARVAL Drosophila melanogaster. - Vanderveken, M.; O'Donnell, M.J. (Archives of Insect Biochemistry and Physiology, 2014)
Recent studies have identified paracrine and endocrine cells in the midgut of larval Drosophila melanogaster as well as midgut and hindgut receptors for multiple neuropeptides implicated in the control of fluid and ion balance. Although the effects of diuretic factors on fluid secretion by isolated Malpighian tubules of D. melanogaster have been examined extensively, relatively little is known about the effects of such factors on gut peristalsis or ion transport across the gut. We have measured the effects of diuretic hormone 31 (DH31), drosokinin and allatostatin A (AST-A) on both K(+) transport and muscle contraction frequency in the isolated gut of larval D. melanogaster. K(+) absorption across the gut was measured using K(+) -selective microelectrodes and the scanning ion-selective electrode technique. Allatostatin A (AST-A; 1 ?M) increased K(+) absorption across the anterior midgut but reduced K(+) absorption across the copper cells and large flat cells of the middle midgut. AST-A strongly inhibited gut contractions in the anterior midgut but had no effect on contractions of the pyloric sphincter induced by proctolin. DH31 (1 ?M) increased the contraction frequency in the anterior midgut, but had no effect on K(+) flux across the anterior, middle, or posterior midgut or across the ileum. Drosokinin (1 ?M) did not affect either contraction frequency or K(+) flux across any of the gut regions examined. Possible functions of AST-A, DH31, and drosokinin in regulating midgut physiology are discussed.